The Apocalypse Unveiled: Reflections on the Reception History of Revelation. (March 2014) - Boxall, Ian
The Book of Revelation has been subject to diverse and sometimes conflicting interpretations across the centuries. The tendency of historical-critical scholars has been to dismiss many of these as eisegesis rather than exegesis. This article surveys the main stages in the reception history of John's visionary book, and attempts to categorise these diverse readings and highlight similarities between them. It considers how the Apocalypse has been adaptable enough to speak to Christians facing persecution from imperial Rome of the second and third centuries or papal Rome of the sixteenth, monastics in the settled period of Byzantium and the medieval West, those seeking insight into the future course of history, and marginalised readers challenging the political status quo. It is argued that this rich impact – in art and music as well as formal commentary – is to be expected of a book which is highly allusive, and which combines a variety of different genres. Like the four living creatures John sees around the throne, Revelation is an unstable book which cannot easily be tamed.